2019
DOI: 10.1080/23279095.2019.1576180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korsakoff Amnesia on performance and symptom validity testing

Abstract: Performance validity tests (PVTs) and Symptom validity tests (SVTs) are developed to identify people that present false or exaggerated symptoms. Although a key factor of both types of tests includes relative insensitivity to cognitive disorders, the direct effects of amnesia have been poorly studied. Therefore, a sample of 20 patients diagnosed with Korsakoff Amnesia (KA) through neuropsychological assessment and 20 healthy comparisons (HC) were administered the Test of Memory Malingering (TOMM), the Structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
5
1
Order By: Relevance
“…This was despite there being a much higher proportion of severely injured cases, a lower proportion of outpatient assessments, and much greater cultural diversity in the current sample, which attests to the robustness of this finding within the brain injury rehabilitation setting. It is also in line with the base rates reported in many smaller studies of other clinical groups, including stroke (Bodner et al, 2019), Korsakoff's syndrome (Oudman et al, 2020), Huntington's disease (Sieck et al, 2012), mild cognitive impairment (Walter et al, 2014), and HIV (Paul et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…This was despite there being a much higher proportion of severely injured cases, a lower proportion of outpatient assessments, and much greater cultural diversity in the current sample, which attests to the robustness of this finding within the brain injury rehabilitation setting. It is also in line with the base rates reported in many smaller studies of other clinical groups, including stroke (Bodner et al, 2019), Korsakoff's syndrome (Oudman et al, 2020), Huntington's disease (Sieck et al, 2012), mild cognitive impairment (Walter et al, 2014), and HIV (Paul et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…33 34 Oudman et al reported that 2 (10%) of 20 individuals with Korsakoff Amnesia failed the second trial of the TOMM. 35…”
Section: Acquired Brain Injurymentioning
confidence: 99%
“…Even in patients with severe (memory) impairments, such as patients suspected of KS. Oudman et al (2020) also examined the performance on PVTs in patients with KS, using the TOMM (Trial 2, cutoff <45) and VAT-E (cutoff values according to Meyer et al, 2017, i.e. Immediate Recognition ≤ 21, Delayed Recognition ≤ 20, Consistency ≤ 21 and Free Recall ≥ 7 in combination with Multiple Choice ≤ 9).…”
Section: Discussionmentioning
confidence: 99%
“…As several patient groups, such as patients with (some types of) dementia (Bortnik et al, 2013;Burton et al, 2015) or patients with moderate-to-severe acquired brain injury (Allen et al, 2007;Macciocchi et al, 2006), are associated with high levels of PVT failure (i.e., false positives), it is expected that patients with KS would show high PVT failure rates as well. Oudman et al (2020) were the first to examine the performance of a small sample of patients with KS (N = 20) on PVTs (i.e., TOMM and VAT-E). They found that PVT task performance was lower for the TOMM and VAT-E in patients with KS compared with healthy controls and did lead to 5%-45% false-positive scores on the PVT subscales.…”
mentioning
confidence: 99%
See 1 more Smart Citation